Whole genome sequence analysis of the first reported isolate of Salmonella Agona carrying blaCTX-M-55 gene in Brazil - Amanda Maria de Jesus Bertani; Thais Vieira; Alex Domingos Reis; Carla Adriana dos Santos; Elisabete Aparecida de Almeida; Carlos Henrique Camargo; Monique Ribeiro Tiba Casas (Scientific Reports, 2023)
Abstract This study analyzes the genomic findings of the first report of Salmonella isolate carrying the bla CTX-M-55 gene, recovered from a bacteremic patient from Brazil. A bacterial isolate positive for the bla CTX-M-55 gene was submitted to antimicrobial susceptibility testing by disk diffusion and epsilometric test. Whole genome sequencing was performed using Illumina technology. Conjugation assay was performed; plasmid sizes determined by S1-PFGE and plasmid content were investigated by hybrid assembly after MinION long reads sequencing. Isolate 288_18 was identified as sequence type ST13, resistant to ampicillin, cefotaxime, ceftazidime, cefepime, ceftriaxone, and aztreonam. A transferable IncFII plasmid sized approximately 67 kb was found to carry the bla TEM-1 and bla CTX-M-55 in a module consisting of IS26-bla TEM-1B -WbuC-bla CTX-M-55-IS26. In addition, an 117 kb IncI1plasmid was also identified in the 288_18 isolate, but without additional resistance genes. To the best of our knowledge, this is the first report of bla CTX-M-55 in Salmonella isolated from human infection in Brazil. The occurrence of bla CTX-M-55 in the IncFII epidemic plasmid in a relevant clinical human isolate of Salmonella Agona underscores the urgent need for enhanced and effective continuous surveillance for controlling its dissemination.